Common and Rare Complications of Lichtenstein Inguinal Hernioplasty - Grelowska, Aleksandra; Ołubiec, Adrian; Oto, Aleksandra; Ejsner, Rafał; Kaczmarek, Julia; Barczyńska, Katarzyna; Błażuk Michał; Poznańska, Nela; Sys, Tomasz (Quality in Sport, 2026)
Inguinal hernia repair remains one of the most frequently performed surgical procedures globally, with approximately 20 million operations conducted annually. While the Lichtenstein tension-free technique using polypropylene mesh is considered the "gold standard" due to its low recurrence rates and high safety profile, the procedure is still associated with a spectrum of potential complications. The most common among these include localized hematomas, seromas, surgical site infections and chronic pain. Furthermore, surgical manipulation within the spermatic cord may result in significant testicular complications. Certain outcomes, such as mesh migration or late-onset infections, may arise many years following the initial intervention. The primary strategy for mitigating these issues lies in the meticulous selection and execution of appropriate operative techniques. Rehabilitation includes early mobilization to the restoration of full physical activity. This study aims to provide a comprehensive review of the diverse range of complications associated with Lichtenstein inguinal hernioplasty.